Phytochemical Composition, Antioxidant Activity and HPLC Fingerprinting Profiles of Three Pyrola Species from Different Regions - Wang, Dongmei; He, Fengyuan; Lv, Zhenjiang; Li, Dengwu (PLOS ONE, 2014)
The present study was performed to investigate the variation of phytochemical composition, antioxidant activity and High Performance Liquid Chromatography (HPLC) fingerprinting profiles of three Pyrola species. Thirteen samples (eight P. decorata, three P. calliantha and two P. renifolia) were collected from different regions in China. The tannin, hyperoside and quercetin contents of all samples were determined by reverse-phase HPLC and varied within the range 9.77–34.75, 0.34–2.16 and 0.062–0.147 mg/g dry weigh, respectively. Total flavonoid content was evaluated and varied within the range 16.22–37.82 mg/g dry weight. Antioxidant activity was determined by DPPH assay, with IC50 ranging from 7.96 to 50.33 µg/ml, ABTS•+ and FRAP assay, within the range 612.66–1021.05 and 219.64–398.12 µmol equiv. Trolox/g, respectively. These results revealed that there were significant variations in phytochemical profiles and antioxidant activity among all samples. Due to the higher phytochemical content and significant antioxidant activity, P. calliantha was selected as the most valuable species, and the P. calliantha sample from Left banner of Alxa even possessed the strongest antioxidant activity among all the thirteen samples. Futhermore, Emei Mountain was proved to be the most suitable region for producing P. decorata. Moreover, in order to further evaluate the diversities and quality of Pyrola, HPLC fingerprint analysis coupled with hierarchical cluster and discrimination analyses were introduced to establish a simple, rapid and effective method for accurate identification, classification and quality assessment of Pyrola. Thirteen samples were divided into three groups consistent with their morphological classification. Two types of discriminant functions were generated and the ratio of discrimination was 100%. This method can identify different species of Pyrola and the same species from different regions of origin. Also, it can be used to compare and control the quality of Pyrola and other natural products prepared from them.